The role of ubiquitination in spinal and bulbar muscular atrophy - Sengupta, Medha; Pluciennik, Anna; Merry, Diane E. (Frontiers in Molecular Neuroscience, 2022)
Spinal and bulbar muscular atrophy (SBMA) is a neurodegenerative and neuromuscular genetic disease caused by the expansion of a polyglutamine-encoding CAG tract in the androgen receptor (AR) gene. The androgen receptor is an important transcriptional regulator of the nuclear hormone receptor superfamily; its levels are regulated in many ways including by ubiquitin-dependent degradation. Ubiquitination is a post-translational modification which plays a key role in both AR transcriptional activity and its degradation. Moreover, the ubiquitin-proteasome system (UPS) is a fundamental component of cellular functioning and has been implicated in diseases of protein misfolding and aggregation, including polyglutamine (polyQ) repeat expansion diseases such as Huntington’s disease and SBMA. In this review, we discuss the details of the UPS system, its functions and regulation, and the role of AR ubiquitination and UPS components in SBMA. We also discuss aspects of the UPS that may be manipulated for therapeutic effect in SBMA.